A STUDY ON INVESTOR’S RISK CAPACITY AND THEIR INVESTMENT DECISION MAKING (International Journal of Food and Nutritional Sciences, 2022)
There are numerous varieties of financial products that are currently on the market has given individual investors a very broad range of investment possibilities. The process of making investment decisions is very important and is affected by a variety of variables. The level of risk absorption that an individual is capable of is a crucial concept that must be understood. Risk, ambiguity, and choice overload are three extremely complex variables that investors must consider when making an investment decision. Financial experts, seasoned investors, and ordinary private families in particular struggle with these. When making financial decisions, investors must pursue certain risks. This may result in high return of money or low return of money. The study was conducted in Kanniyakumari district of Tamil Nadu. The sample size of the study was 150 respondents. The main of this study is to evaluate the risk capacity of the investors and their investment decision making.